Analysis of the Influence of Capital Expenditure on the Economic Growth of Baubau City - Dwi Agustyawati; Nur Zarliani Uli; Faisal Setiawan Farisman; Selvi Anggraini (Jurnal Ekonomi Balance, 2025)
This study aims to analyze the influence of capital expenditure on economic growth in Baubau City. Capital expenditure is a crucial component of regional government spending, particularly in supporting infrastructure development and the provision of public assets that generate long-term economic benefits. This research employs a quantitative approach using secondary data obtained from the Regional Financial and Asset Management Agency (BPKAD) of Baubau City and the Central Bureau of Statistics (BPS) for the period 2018–2022. The data include realized capital expenditure and Gross Regional Domestic Product (GRDP) as a proxy for economic growth. Simple linear regression analysis is applied to examine the relationship between capital expenditure and economic growth, supported by classical assumption tests to ensure the reliability of the regression model. The empirical results indicate that capital expenditure has a statistically significant effect on economic growth in Baubau City, with a significance value of 0.000, which is lower than the 0.05 threshold. This finding confirms that increased capital expenditure contributes positively to regional economic performance by stimulating economic activity through a multiplier effect. Investments in fixed assets and infrastructure enhance production capacity, support key economic sectors, and encourage regional development. Overall, the study highlights the strategic role of capital expenditure in promoting sustainable economic growth at the regional level. The findings provide valuable insights for local governments in optimizing budget allocation policies to support economic development and improve regional welfare